EEnergy Efficiency Analysis of an Electric Furnace through the Implementation of a Forced Convection Fan - Isaac Simbaña; Sarai Mena; Silvana Chasipanta (Revista Técnica Energía, 2025)
This study presents an energy efficiency analysis of an electric furnace used for tempering heat treatments by implementing a forced convection fan. Improving energy efficiency in industrial heating systems remains a critical challenge, driven by the need to lower operational costs and enhance sustainability. A numerical model was developed based on heat transfer mechanisms, applying computational fluid dynamics (CFD) with a mesh of 138 565 elements and a validated mesh quality factor of 4.681. The continuity, momentum, and energy conservation equations were analyzed under real operating conditions. Results indicated that the maximum temperature increased from 290 to 327.2 K with the addition of the fan, while electrical consumption rose by only 1.54%, corresponding to an additional cost of merely USD 0.0005 per operating cycle. This thermal enhancement promotes greater temperature uniformity and reduces operational times. Consequently, integrating a forced convection system in industrial electric furnaces proves to be a technically and economically viable strategy.